Pushing the limits of lithium bis(oxalate)borate/acetonitrile using 1-ethyl-3-methylimidazolium tetrafluoroborate for supercapacitors - Hamenu, Louis; Madzvamuse, Alfred; Hu, Mengyang; Mohammed, Latifatu; Bon, Chris Yeajoon; Kim, Sang Jun; Cho, Won Il; Park, Jongwook; Ko, Jang Myoun (ELSEVIER SCIENCE BV, 2017)
Supercapacitors provide us with enormous power output for energy storage. Their energy output however still remains quite low compared to other energy storage materials like the batteries. This paper reports a highly stable liquid electrolyte which is composed of mixtures of 1-ethyl-3-methylimidazolium tetrafluoroborate(EMIBF4) ionic liquid with highly stable lithium bis(oxalate) borate LiBOB/acetonitrile( ACN). The electrolytes display remarkable supercapacitive performance at a high voltage of 3 V. The electrochemical impedance spectroscopy shows that EMIBF4 helps to reduce the bulk resistance and charge transfer resistance across the electrode surfaces by facilitating high ionic diffusions across the electrode/electrolyte interface. The high stability and high ionic conductivity of the electrolytes reflected in the good cycling performance tests at 2.8 V with a maximum delivery capacitance of 19.5Fg(-1) after 1000cycles at a high scan rate of 200 mVs(-1). (C) 2017 Elsevier B.V. All rights reserved.
Keywords: SOLID-STATE SUPERCAPACITORS; IONIC LIQUIDS; POLYMER ELECTROLYTES; ENERGY-STORAGE; PERFORMANCE; LIBOB; CONDUCTIVITY; ELECTRODES; BATTERY